Crosslinked Aromatic Polyimides for High-Performance Heat-Dissipation Materials - Park, Hyeon-Woo; Lee, Miyeon; Kim, Seo Gyun; Ku, Bon-Cheol; Jang, Se Gyu; Kim, Byoung-Suhk; You, Nam-Ho (WILEY, 2025)
In this work, polyimide (PI) with high thermal stability was utilized as a precursor to prepare graphite films with high thermal conductivity. Aromatic PIs containing acetylene units in their backbone were synthesized through the condensation polymerization of 4,4 '-(ethyne-1,2-diyl)diphthalic anhydride (EBPA), 4,4 '-biphthalic anhydride (BPDA), and 3,3 '-dihydroxybenzidine (DHB). Under a heat treatment, the acetylene units in the PI structure form crosslinked bonds within the polymer main chain via a cycloaddition reaction. This crosslinking enhances thermal stability and increases char yield. The grain size, crystallinity, and thermal conductivity of the resulting graphite films were analyzed. Notably, the graphite film derived from the PI precursor with the highest acetylene unit content demonstrated high density (2.221 g/cm3), a large grain size (130.14 nm), and excellent thermal conductivity (1334 W/mK).